Uniformly Grafting SnO2 Nanoparticles on Ionic Liquid Reduced Graphene Oxide Sheets for High Lithium Storage. Issue 9 (26th February 2018) - Zhu, Shengming; Dong, Xufeng; Gao, Song; Jin, Xiaozhe; Huang, Hao; Qi, Min
Abstract: SnO2 ‐based anode materials for lithium ion batteries suffer from inevitable pulverization and electrical disconnection during repeated charge–discharge cycles. Stabilizing nanostructure of SnO2 particles by graphene is one of the most extensively studied strategies to achieve high capacity and long‐term cyclability. However, in the wet chemistry, the reaggregation of the solvent–dispersed graphene and the SnO2 make it difficult to fabricate SnO2 /graphene composites with desirable nanostructure which can be maintained during lithiation. Herein, the ionic liquid‐assisted method is applied to prepare SnO2 nanoparticles grafted on ionic liquid reduced graphene oxide (SnO2 @IL‐RGO) composite through a novel "bridging effect" generated from the interaction between these two constituents and ionic liquid which efficiently maintains the desirable nanostructure and offers more conductive pathway upon cycling. The composite as an anode material achieves an increasing capacity up to 1508 mAh g −1 in the 427th cycle at high current of 1 A g −1 . The ionic liquid‐assisted strategy may be a promising approach to promote the strong combination and uniform dispersion of other metal oxides on the carbonaceous materials, providing a new way to prepare metal oxide–carbon composites for wide applications. Abstract : SnO2 @ionic liquid reduced graphene oxide is prepared with SnO2 particles strongly and uniformly bound on carbonaceous sheets. The composite exhibits the lamellar structure of the carbonaceous sheets uniformly decorated by spherical‐shaped SnO2 nanoparticles which can be efficiently maintained upon cycling, avoiding the inevitable pulverization of SnO2 ‐based electrode with electric contact loss which provides more reactive sites for Li storage.